The Main Disease and its Attacks in the Generative Phase of Maize (Zea Mays L) in the Freshwater Swamps of South Sumatra - Harman Hamidson; Riski Anwar Efendi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
In South Sumatra, the ​​freshwater swamps is 157,846 hectares, with this wide freshwater swamps, it can be used for crops food  cultivation, one of which is maize. The purpose of this study was to provide information on the identification and attack of maize disease in freshwater swamps of South Sumatra. The research method was purposive sampling. The results of the study identification that the symptoms of maize leaf rust attack, seen from the physiology of maize leaves, were the lumps or pustules of orange color such as rust and the symptoms of maize leaf blight seen from the physiology of maize leaves, were small oval brownish lines like burning leaves. The leaf rust disease had an attack rate of 90% and the maize leaf blight reached 98%. Based on the results of this study, the main disease of maize attacking in the generative phase was the leaf rust (Puccinia polysora) and maize leaf blight (Bipolaris maydis).